Impact of cholesterol in encapsulated vitamin E acetate within cocoliposomes - Hudiyanti Dwi; Hidayati Salma Nur; Siahaan Parsaoran; Ngadiwiyana Ngadiwiyana; Nur Abidin; Sari Ratna Indria; Amalia Indrian Rizka; Christa Sherllyn Meida; Patrechia Amanda Chindy; Maharani Adinda Eka (Open Chemistry)
Vitamin E acetate (VEA) is commonly used in manufacturing pharmaceuticals, food additives, and animal feeds. However, VEA possesses disadvantages, including low water solubility, low bioavailability, and susceptibility to degradation and oxidation. This study investigated the use of cocoliposomes for encapsulating VEA (VEACL). The cocoliposomes consisted of coconut phospholipids (CocoPLs) and cholesterol (Chol). Several parameters, such as functional groups, transition temperature, encapsulation efficiency (EE), release profile, particle size, polydispersity index, and zeta potential, were analyzed to evaluate the impact of cholesterol inclusion on the cocoliposome membrane. The results show that the Fourier transform infrared spectra of VEACL do not exhibit any new, distinct peaks that differ from the peaks of its constituent composition. Therefore, it confirmed that no chemical reactions occurred during the manufacturing of VEACL. Cholesterol in the system raises the transition temperature of phospholipids and enhances the stability of VEACL. The EE remains above 80% despite a 20% increase in cholesterol levels. The release rate of VEA from cocoliposomes was slower with VEACL–20%Chol compared to VEACL–0%Chol. The cholesterol level leads to a decrease in particle size and an increase in the negative zeta potential of the cocoliposomes. Data show that cocoliposomes are effective carriers for VEA encapsulation.